Social Rights and the Turkish Constitutional Court - Engin Yıldırım (The Constitutional Court of the Republic of Indonesia, 2021)
Through a brief examination of the Turkish experience, this article endeavors to illuminate the debate on the role of constitutional courts in interpreting social rights. The Turkish Constitutional Court has in many cases rejected applications for the annulment of legislation related to social rights, on the grounds that it is within the legislature’s discretion to determine public policy priorities based on economic resources and economic stability. This article suggests the Turkish Constitutional Court has narrowly interpreted constitutionally recognized social rights within the boundaries of the Turkish Constitution, with the notable exception of labor rights in individual applications.